Economic Policy and the Movement of Factories in the German Sphere of Influence during World War II (1943/44) - the Role of Lower Silesia and the Eastern German Territories = Polityka gospodarcza i zmiana lokalizacji zakładów w niemieckie j sferze wpływów podczas drugiej wojny światowej - rola Dolnego Śląska i byłych wschodnich terenów Rzeszy Niemieckiej - Kouli, Yaman (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Relocation of industrial plants, which were significant for the production of armaments during the war, is a subject of economic history of Germany that received little research coverage so far. After the war claims would often arise that most of the plants were moved to the east of the Reich, mostly to the terrains of Lower Silesia, to protect them from the air raids. That interpretation is partially true, but it is also incomplete.
Keywords: czasopismo; czasopismo akademickie; Ziemie Zachodnie; stosunki polsko-niemieckie; pogranicze polsko-niemieckie; historia